Gender bias in consumer perceptions: The case of agro-input dealers in Uganda - De, Anusha; Miehe, Caroline; Van Campenhout, Bjorn (International Food Policy Research Institute, 2022)
Faced with incomplete and imperfect information, economic actors rely predominantly on perceptions and often base decisions on heuristics prone to bias. Gender bias in perceptions favoring men has been found in a wide variety of settings and may be an important reason why some sectors remain dominated by men and gender gaps persist. Using ratings of agro-input dealers provided by smallholder farmers in their vicinity, we test if farmers perceive male-managed agro-input shops differently than agro-input shops managed by women. After controlling for observable characteristics at the input dealer level and including fixed effects to account for farmer-level heterogeneity, we find that farmers rate male-managed agro-input outlets higher on a range of attributes related to the dealership in general, as well as when farmers are asked to consider the quality of inputs sold by the dealer. Our results suggest that consumers' biased perceptions continue to be an important entry barrier for women in the subsector, and we conclude that policies and interventions designed to challenge gender norms and customs are needed to correct bias in perceptions.